Tungsten-induced synthesis of defective palladium–copper–tungsten trimetallic nanochains to highly enhance activity for formic acid electrooxidation. (December 2020) - Zhang, L.Y.; Meng, X.; Wu, H.; Wang, F.; Huang, H.; Ouyang, Y.; Yuan, W.; Guo, C.X.; Li, C.M.
Abstract: Great efforts have been devoted to the exploration of PdCu-based catalysts toward formic acid oxidation, but their activity is still much lower than that expected. In this work, nanotwin-rich PdCuW trimetallic nanochains were successfully fabricated using a modified polyol method. The formation of crystalline defect of nanotwins should be related to the significant lattice mismatch among Pd, Cu, and the introduced W. It is discovered that the nanotwins could function as superb active sites to highly improve the peak current density of formic acid oxidation. In addition, the W- and Cu-tailored PdCuW nanochains optimize the electronic structure of Pd with suitable binding energy to reduce the charge-transfer resistance, resulting in greatly enhanced catalytic activity. This work highlights the beauty of the architecture with introduced W to significantly enhance catalytic performance in particular the activity of formic acid electrooxidation. Graphical abstract: Image 1 Highlights: Nanotwin-rich PdCuW trimetallic nanochains are successfully synthesized. The introduced W induces the formation of crystalline defect of nanotwins. The introduced W could significantly modulate the electronic structure of Pd. PdCuW nanochains exhibit 4.9-fold higher oxidation peak current density than Com Pd/C.